Change in Contrast Sensitivity among Patients with Diabetic Mellitus Type II - Shrestha, Sabina; Prasai, Gunjan; Shrestha, Reshma; Malla, Om Krishna (Birat Journal of Health Sciences, 2022)
Introduction: Eye being one of the target organs of diabetes mellitus has many pathological consequences, one possibly being contrast sensitivity. Contrast sensitivity is required for daily activities like in situations of low light, fog or driving at night. The study was conducted to find out contrast sensitivity among diabetic Methodology: A hospital based descriptive cross- sectional study of contrast sensitivity was conducted among type II diabetics with or without retinopathy at Kathmandu Medical College from April to December 2018. Patient demographics and comprehensive clinical examinations findings were recorded in a specially designed proforma. Convenience sampling was done and informed consent was taken. Leas symbol low contrast test 10M was used for contrast sensitivity testing. The contrast levels of the test lines on the five pages are 25%, 10%, 5%. 2.5%and 1.2%. Data was analyzed in excel and SPSS (version21). Results were expressed in frequency, percentage and mean as required. Association of contrast sensitivity with age, gender, duration of diabetes, blood sugar level and diabetic retinopathy was tested using chi square test. Results: Among the 45 study population, female to male ratio was 1:2. Age ranged from 25 to 76 years with maximum patients in the age group 51-60 years. Blood sugar was controlled in 33.33%. Contrast sensitivity was decreased in 40%. Among the patients with decreased contrast sensitivity, blood sugar was uncontrolled in 66.67%. Similarly, 72.2% of participants with decreased contrast sensitivity had no diabetic retinopathy. The association of contrast sensitivity with age of the patient, gender, duration of diabetes mellitus, blood sugar level and diabetic retinopathy was not statistically significant with p values 0.34, 0.52, 0.07, 1 and 0.89 respectively. Conclusion: Contrast sensitivity can be decreased among patients with type II diabetes mellitus irrespective of gender, age of the patient, duration of diabetes, control of blood sugar and presence or absence of diabetic retinopathy.